ANALISIS KINERJA RUMAH SAKIT BERDASARKAN BALANCED SCORECARD DI RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU - Arpita Arpita; Amries Rusli Tanjung; Nasrizal Nasrizal (PEKBIS, 2019)
Hospitals have a role in providing professional and quality health services that areaffordable to all levels of society, and provide basic health services and advancedhealth services according to hospital classes and prescribed standards. A Hospitalsneed good performance to achieve that goals, An assessment of of comprehensiveperformance in the financial and non-financial aspects is needs to find out and toincrease a hospital performance. This reseach introduced balanced scorecardmethod as a management tool in measuring its performance which includes financialperspective, customer perspective, internal business process perspective andgrowth and learning perspective. RSUD Arifin Achmad is Regional Public ServiceAgency. This reseach aims to determine the performance achievement of ArifinAchmad Hospital during the period of 2015-2017 by using four BSC perspectivesand see the relationship between the four perspectives. The type of research used ismixed methods, which is a research step by combining quantitative and qualitativeresearch, secondary data and primary data. The results of the reseach showed thatthe performance 2015 showed a score of 78.28, 2016 with a score of 79.03, and2017 with a score of 79.78. These three years the assessment of interpretation A(Very Good) and can be seen that the increase in performance has been gettingbetter even though improvements will continue to be carried out in various types ofservices and by measuring various indicators..